2015
DOI: 10.1137/140978880
|View full text |Cite
|
Sign up to set email alerts
|

Network-Based Vertex Dissolution

Abstract: We introduce a graph-theoretic vertex dissolution model that applies to a number of redistribution scenarios such as gerrymandering in political districting or work balancing in an online situation. The central aspect of our model is the deletion of certain vertices and the redistribution of their load to neighboring vertices in a completely balanced way. We investigate how the underlying graph structure, the knowledge of which vertices should be deleted, and the relation between old and new vertex loads inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Naturally, however, it has been mainly explored in the political science arena [Erikson, 1972], primarily based on analysis of past elections [Grofman et al, 1997;Tangian, 2010;Felsenthal and Miller, 2015] -trying to figure out if it occurred, and trying to calculate some measure of its effects. In the past few years the computational social choice community has also taken interest in this topic, on issues such as worst case analysis of how districts effect voting rules [Bachrach et al, 2016], and the computational complexity of gerrymandering [Lewenberg et al, 2017;van Bevern et al, 2015]. Recently, [Pegden et al, 2017] suggested a "cut and choose"like mechanism to divide districts in practice.…”
Section: Related Workmentioning
confidence: 99%
“…Naturally, however, it has been mainly explored in the political science arena [Erikson, 1972], primarily based on analysis of past elections [Grofman et al, 1997;Tangian, 2010;Felsenthal and Miller, 2015] -trying to figure out if it occurred, and trying to calculate some measure of its effects. In the past few years the computational social choice community has also taken interest in this topic, on issues such as worst case analysis of how districts effect voting rules [Bachrach et al, 2016], and the computational complexity of gerrymandering [Lewenberg et al, 2017;van Bevern et al, 2015]. Recently, [Pegden et al, 2017] suggested a "cut and choose"like mechanism to divide districts in practice.…”
Section: Related Workmentioning
confidence: 99%
“…Notably, the study of Gerrymandering over graphs, which is pretty much analogous to our setting, very recently gained significantly increased interest by various research groups [4,11,18,21]. A similar model for graph-based redistribution scenarios and political districting has been studied under the name "network-based vertex dissolution" [5].…”
Section: Related Workmentioning
confidence: 99%
“…Borodin et al (2018) investigated how geographic spread affects gerrymandering ability, though those results are mostly empirical. Furthermore, there is a whole line of research on allowing agents to move between districts, a form of "reverse gerrymandering," that has also been investigated in the past few years (see, Bervoets and Merlin (2012); van Bevern et al (2015); Lev and Lewenberg (2019)).…”
Section: Related Workmentioning
confidence: 99%